2000
DOI: 10.1086/303078
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in the Rett Syndrome Gene, MECP2, Causes X-Linked Mental Retardation and Progressive Spasticity in Males

Abstract: Heterozygous mutations in the X-linked MECP2 gene cause Rett syndrome, a severe neurodevelopmental disorder of young females. Only one male presenting an MECP2 mutation has been reported; he survived only to age 1 year, suggesting that mutations in MECP2 are male lethal. Here we report a three-generation family in which two affected males showed severe mental retardation and progressive spasticity, previously mapped in Xq27.2-qter. Two obligate carrier females showed either normal or borderline intelligence, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
138
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(145 citation statements)
references
References 15 publications
5
138
0
2
Order By: Relevance
“…In addition, MECP2 mutations have been associated with non-RTT phenotypes, including neonatal onset encephalopathy in males, either as a germline [Villard et al, 2000;Imessaoudene et al, 2001] or somatic [Clayton-Smith et al, 2000] mutation, an Angelman-like phenotype [Watson et al, 2001], mild nonspecific mental retardation [Orrico et al, 2000;Yntema et al, 2002], and X-linked mental retardation pedigrees [Meloni et al, 2000;Dotti et al, 2002;Klauck et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MECP2 mutations have been associated with non-RTT phenotypes, including neonatal onset encephalopathy in males, either as a germline [Villard et al, 2000;Imessaoudene et al, 2001] or somatic [Clayton-Smith et al, 2000] mutation, an Angelman-like phenotype [Watson et al, 2001], mild nonspecific mental retardation [Orrico et al, 2000;Yntema et al, 2002], and X-linked mental retardation pedigrees [Meloni et al, 2000;Dotti et al, 2002;Klauck et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…However, MECP2 gene mutations were identified in males affected with a broader range of neurodevelopmental phenotypes. 13,14 Hemizygous MECP2 point mutations that inactivate the protein are associated with a severe neonatal encephalopathy phenotype in affected males. 15 When such mutations occur in males with somatic mosaicism or a 47, XXY karyotype, the presentation is more consistent with a classic Rett phenotype because of a compensating normal X-chromosome.…”
mentioning
confidence: 99%
“…16 -18 Hypomorphic mutations, which barely cause a phenotype in females, cause mental retardation, tremors, and a variety of neuropsychiatric features in affected males. 13,19,20 More recent clinical testing for MECP2 gene rearrangements revealed that entire MECP2 gene duplications occur in some males manifesting a progressive neurodevelopmental syndrome. [21][22][23] Diagnostic studies at the Baylor Medical Genetics Laboratories have identified seven affected males with increased copynumber of the MECP2 gene.…”
mentioning
confidence: 99%
“…The phenotypes of the three female patients were consistent with those of RTT but the five males not. To our knowledge, only about 28 familial cases with MECP2 mutations have been reported (Augenstein et al, 2009; Couvert et al, 2001; Dayer et al, 2007; Evans et al, 2006; Kankirawatanaet al, 2006; Khajuria et al, 2012; Klauck et al, 2002; Lambert et al, 2016; Meloni et al, 2000; Moog et al, 2006; Orrico et al, 2000; Ravn et al, 2011; Villard, 2007; Yntema et al, 2002), with genotypic mutations including missense, frameshift, and nonsense mutations, intragenic deletions and copy number variations (CNV). The phenotypes of those mutation carriers manifested from classical RTT congenital encephalopathy, nonspecific XLMR, and to clinically asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, anecdotal reports over the past decades accumulated only approximately 28 reports in literature (Augenstein, Lane, Horton, Schanen, & Percy, 2009; Couvert et al, 2001; Dayer et al, 2007; Evans, Archer, Whatley, & Clarke, 2006; Kankirawatana et al, 2006; Khajuria et al, 2012; Klauck et al, 2002; Lambert et al, 2016; Meloni et al, 2000; Moog et al, 2006; Orrico et al, 2000; Ravn et al, 2011; Villard, 2007; Yntema et al, 2002). In this paper, we report Chinese familial cases of eight children and their six mothers with MECP2 mutations, and address their clinical and molecular characteristics and its possibly underlying genetic mechanisms.…”
Section: Introductionmentioning
confidence: 99%